(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
This study aims mainly to identify the role of the use of blockchain technology in improving the quality of digital financial reports, answering questions and testing the hypothesis of the study, the researchers relied on the descriptive analytical approach, and to obtain the necessary data a questionnaire was distributed after evaluation to the study community. The results of the study have shown that the use of blockchain technology helps to provide a high degree of reliability in digital financial reports published to banks over the Internet, ensure the speed of completion and completion, and maintain the privacy and confidentiality of the information contained in the digital financial reports of banks and see them anytime, anywhere. The study recommended the need to move towards the use of blockchain technology because it is a secure cloud network, through which transactions and trades are recorded and executed, in addition to crypto currencies, where these trades are conducted quickly, safely and effectively, and characterized by the preparation of financial reports characterized by transparency and high reliability, due to informing all the parties of the network concerned with the details of each transaction and each trade.